Vibration analysis of a multi-span continuous bridge subject to complex traffic loading and vehicle dynamic interaction - Wang, Lingbo; Kang, Xin; Jiang, Peiwen (KSCE journal of civil engineering, 2016)
A numerical analysis of the dynamic behavior of multi-span continuous bridges subject to traffic loadings and vehicle dynamic interactions is presented in this paper using the finite element program ANSYS. The proposed numerical model is capable of: (1) analyze “complex bridge systems”, “complex vehicle models”, and “complex traffic conditions”; (2) predict the vehicle-bridge coupled vibration response under various complex traffic loadings and vehicle dynamic conditions including the passage of multiple vehicles, vehicles changing lanes, vehicles subject to constant acceleration, and vehicles overtaking; and, (3) investigate the effect of girder stiffness decay on the coupled vibration of the vehicle-bridge system. Analytical and experimental results indicate that decay in the girder stiffness has a major effect on the coupled vibrations between the vehicles and bridge. The established method could be extended to analyze the vehicle-bridge coupled vibrations of many different types of bridges subject to complex vehicle loadings, which potentially could have a broad impact in the field of Bridge Engineering.